PEMBERIAN AIR SUSU IBU EKSKLUSIF PADA PEREMPUAN PEKERJA DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN PEKANBARU - Rahman, Nurvi Astina; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted at Kelurahan Tuah Karya, Kecamatan Tampan, Pekanbaru. The purpose of this study was to determine the challenge of Exclusive breastfeeding on working women and their drivers and inhibitors. The focus of this research was the Exclusive breastfeeding method in Kelurahan Tuah Karya, Kecamatan Tampan, Pekanbaru. The technique of determining samples in a purposive sampling and set the number of samples as many as 8 people. The author uses qualitative descriptive method and Instrument data was observation, interview and documentation. Research conducted, the authors found that in giving Exclusive breastfeeding to women workers is in three ways: home to brestfeed her baby, milking the workplace and bring the baby to work. The driving factor in exclusive breastfeeding was due to several reasons that female workers have found that: it contains many benefits, hygienic, practical and economical. From this study, although working women always have excuses to exclusively breastfeed their children but they alsoface some obstalcles such as: lack of breastfeeding facilities at work, limited time and physical. Physical factors referred to in this study was the lack of milk production, the pain experienced by the mother. While the time is limited are those who have heavy duty work place so that their task to breastfeed the baby was sometimes become obstructed. Keywords: Exclusive Breastfeeding, Woman Workers, Factor